Validation of the Brazilian version of the childhood asthma control test (c‐ACT). Issue 4 (30th September 2015) - Oliveira, Suelen G.; Sarria, Edgar E.; Roncada, Cristian; Stein, Renato T.; Pitrez, Paulo M.; Mattiello, Rita
Summary: Background: Children's perception of their symptoms has proved reliable and relevant to disease management and should be considered when assessing their asthma control. The aim of the study is to validate the Brazilian Portuguese version of the Childhood Asthma Control Test (c‐ACT) in children aged 4–11 years. Methods: This is a cross‐sectional study in children diagnosed with asthma undergoing treatment in a pediatric pulmonology outpatient clinic in Porto Alegre, Brazil. The translation and linguistic adaptation of the instrument were performed in accordance with international recommendations for questionnaire validation. Results: A total of 105 participants were included, aged 4–11 years. Validity: all correlations between the total score and items on the questionnaire were significant and obtained values of r ≥ 0.3, and c‐ACT means showed statistically significant differences between the GINA categories ( P  < 0.01). The controlled asthma group showed significantly higher c‐ACT scores than those of uncontrolled asthma group (controlled 22.0 ± 2.9 vs. uncontrolled 16.3 ± 5.3 P  < 0.01); and partially controlled asthma group showed significantly higher c‐ACT scores than those of uncontrolled asthma group (partially controlled 20.0 ± 4.0 vs. uncontrolled 16.3 ± 5.3 P  = 0.03). Correlations between the c‐ACT total score and spirometry and nitric oxide were poor (r = 0.020; P  = 0.866 and r = 0.035; P  = 0.753, respectively). Reliability: the α–C coefficient for the c‐ACT total score was 0.677 (95%CI 0.573–0763). Sensitivity to change had an effect size of 0.8 and an intraclass correlation coefficient of 0.598. No floor or ceiling effects were observed. Conclusion: The Brazilian version of the Childhood Asthma Control Test proved to be valid and reliable in children aged 4–11 years.Pediatr Pulmonol. 2016;51:358–363 . © 2015 Wiley Periodicals, Inc.